(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2022)
The following document presents the economic and stock market trajectory of an important Spanish company in the retail sector: International Food Distributor(Dia), during the period that was administrated by Ana María Llopis (2011-2018), the first woman to preside over a non-banking corporation of the select Ibex-35 index; making explicit in this article, through an analysis of the number of female workers and the digital news content (El País, El Mundo, ABC, Expansión, El Economista, Cinco Días…) the divergence between the positive defense of the supossed feminist leadership of this entrepreneur by the Spanish general and economic media and the catastrophic results achieved during his mandate.